Association Between Amyloid and Tau Accumulation in Young Adults With Autosomal Dominant Alzheimer Disease (2018)
ABSTRACT: Importance It is critically important to improve our ability to diagnose and track Alzheimer disease (AD) as early as possible. Individuals with autosomal dominant forms of AD can provide clues as to which and when biological changes are reliably present prior to the onset of clinical symptoms. Objective: To characterize the associations between amyloid and tau deposits in the brains of cognitively unimpaired and impaired carriers of presenilin 1 (PSEN1) E280A mutation. Design, Setting, and Participants: In this cross-sectional imaging study, we leveraged data from a homogeneous autosomal dominant AD kindred, which allowed us to examine measurable tau deposition as a function of individuals’ proximity to the expected onset of dementia. Cross-sectional measures of carbon 11–labeled Pittsburgh Compound B positron emission tomography (PET) and flortaucipir F 18 (previously known as AV 1451, T807) PET imaging were assessed in 24 PSEN1 E280A kindred members (age range, 28-55 years), including 12 carriers, 9 of whom were cognitively unimpaired and 3 of whom had mild cognitive impairment, and 12 cognitively unimpaired noncarriers. Main Outcomes and Measures: We compared carbon 11–labeled Pittsburgh Compound B PET cerebral with cerebellar distribution volume ratios as well as flortaucipir F 18 PET cerebral with cerebellar standardized uptake value ratios in mutation carriers and noncarriers. Spearman correlations characterized the associations between age and mean cortical Pittsburgh Compound B distribution volume ratio levels or regional flortaucipir standardized uptake value ratio levels in both groups. Results: Of the 24 individuals, the mean (SD) age was 38.0 (7.4) years, or approximately 6 years younger than the expected onset of clinical symptoms in carriers. Compared with noncarriers, cognitively unimpaired mutation carriers had elevated mean cortical Pittsburgh Compound B distribution volume ratio levels in their late 20s, and 7 of 9 carriers older than 30 years reached the threshold for amyloidosis (distribution volume ratio level > 1.2). Elevated levels of tau deposition were seen within medial temporal lobe regions in amyloid-positive mutation carriers 6 years before clinical onset of AD in this kindred. Substantial tau deposition in the neocortex was only observed in 1 unimpaired carrier and in those with mild cognitive impairment. β-Amyloid uptake levels were diffusely elevated in unimpaired carriers approximately 15 years prior to expected onset of mild cognitive impairment. In carriers, higher levels of tau deposition were associated with worse performance on the Mini-Mental State Examination (entorhinal cortex: r = −0.60; P = .04; inferior temporal lobe: r = −0.54; P = .06) and the Consortium to Establish a Registry for Alzheimer Disease Word List Delayed Recall (entorhinal cortex: r = −0.86; P < .001; inferior temporal lobe: r = −0.70; P = .01). Conclusions and Relevance: The present findings add to the growing evidence that molecular markers can characterize biological changes associated with AD in individuals who are still cognitively unimpaired. The findings also suggest that tau PET imaging may be useful as a biomarker to distinguish individuals at high risk to develop the clinical symptoms of AD and to track disease progression.